2015
DOI: 10.7196/samjnew.7797
|View full text |Cite
|
Sign up to set email alerts
|

Use of EMLA cream as a topical anaesthetic before venepuncture procedures in field surveys: A practice that helps children, parents and health professionals

Abstract: EMLA cream was safe and effective for alleviating the pain associated with venepuncture in a fieldwork setting. We therefore believe that it merits a place in the routine premedication of children before phlebotomy and cannulation procedures in clinical settings, research studies and field surveys. Further research is recommended to assess whether EMLA cream can be used for immunisations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 12 publications
0
7
0
2
Order By: Relevance
“…[Table 1]. Concerning the outcome variable, pain was measured using the VRS by two studies [16,19] the NRS by one study [18] and the VAS by two studies [17,19]. One of the reviewed studies [19] used two pain scales to measure pain; Oluwadun et al [19] employed the VRS and the VAS for all their participants; van Straten et al [18] on the other, created ordinal categories of patients pain from their NRS scores.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[Table 1]. Concerning the outcome variable, pain was measured using the VRS by two studies [16,19] the NRS by one study [18] and the VAS by two studies [17,19]. One of the reviewed studies [19] used two pain scales to measure pain; Oluwadun et al [19] employed the VRS and the VAS for all their participants; van Straten et al [18] on the other, created ordinal categories of patients pain from their NRS scores.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding adverse effects, all four studies evaluated this outcome, and three observed no adverse reactions [16][17][18] with the various topical interventions. One study [19], on the other hand, discovered more adverse reactions with the 10% lidocaine treatment compared to the 5% EMLA treatment; blanching of the skin was noticed in both the treatment groups and the control group [Table 2].…”
Section: Resultsmentioning
confidence: 99%
“…Systemische Nebenwirkungen sind sehr selten und können nur bei einer deutlichen Überdosierung auftreten. Die Anwendung ist auf die intakte Haut beschränkt 7 .…”
Section: Zaubercreme – Die Haut Schützenunclassified
“…Unfortunately, there are some factors leading to infrequent use of topic local anesthesia. More specifically, it takes considerable time to produce a sufficient effect [ 14 16 ], higher cost [ 17 ], and may cause allergic contact dermatitis [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%